Fatigue is highly associated with poor health‐related quality of life, disability and depression in newly‐diagnosed patients with inflammatory bowel disease, independent of disease activity. Issue 8 (20th February 2014) - Cohen, B. L.; Zoëga, H.; Shah, S. A.; LeLeiko, N.; Lidofsky, S.; Bright, R.; Flowers, N.; Law, M.; Moniz, H.; Merrick, M.; Sands, B. E.
Summary Background Fatigue is common in Crohn's disease (CD) and ulcerative colitis (UC). Data on fatigue in newly diagnosed patients are unavailable. Aim To report prevalence of fatigue in newly diagnosed CD and UC patients and examine its association with health‐related quality of life (HRQOL), depression and disability. Methods The Ocean State Crohn's and Colitis Area Registry (OSCCAR) is a statewide cohort of newly diagnosed inflammatory bowel disease patients in Rhode Island. Fatigue was assessed using the Functional Assessment of Chronic Illness Therapy‐Fatigue Scale. Patients were administered instruments measuring HRQOL, overall disability and work impairment, and depression. Results Fatigue was prevalent in 26.4% of 220 subjects. Cohen's d effect sizes for fatigue were large: Short‐Form 36 Health Survey mental health component (CD 1.5, UC 1.4) and physical health component (CD 1.4, UC 1.4), EuroQol‐5D valuation of current health state (CD 1.2, UC 1.0), Inflammatory Bowel Disease Questionnaire (CD 1.9, UC 1.6) and Patient Health Questionnaire depression scale (CD 1.8, UC 1.7). Fatigued patients reported more work impairment (Score difference: CD 29.5%, UC 23.8%) and activity impairment (score difference: CD 32.3%, UC 25.7%) on the Work Productivity and Activity Impairment Questionnaire. Fatigue's association with all scores remained highly significant despite controlling for disease activity. Conclusions Fatigue is strongly associated with poor HRQOL, disability and depression similarly in CD and UC even when controlling for disease activity. Fatigue's association with a wide range of patient‐reported outcome measures suggests that monitoring fatigue is a simple way to screen for overall disruption in patient life.